Exploring the Role of Religiosity in Human Resource Management Practices: New Implications towards Ensuring Equality and Diversity in Organizations - Abboud, Elsa; Zaidi, Syed Faizan Hussain; Said, Dina; El-Bayaa, Nourhan (Journal of Cultural Analysis and Social Change, 2026)
Achieving equality and respecting diversity in human resource management practices remain an important issue to be addressed in organizations. This paper explores the case of Lebanon, a small country, known for its religious diversity, yet faces challenges in ensuring equality. Within the context of the Middle East region, a limited amount of research explicitly discussed religiosity and its impact on hiring practices. In fact, Lebanon, witnesses a legal allocation of higher positions in governmental institutions according to people’s religious affiliation. Thus, the purpose of this empirical research is to evaluate whether similar practices are also occurring in the recruitment and selection process of private organizations. Based on the social identity theory, a proposed model was analyzed by incorporating survey centered quantitative research methodology and employing structural equation modelling technique. The results have shown that most of the citizens are deeply religious, leading to evident discrimination in employment. The findings contribute to the literature by adding new evidence and knowledge about discrimination in human resource management practices and recommending strategies to ensure equal employment opportunities and more equitable and diverse work environment.